STUDENTS’ VOCABULARY MASTERY TAUGHT USING HANGAROO GAME AND WORD JUMBLE - Meidiana Sabila (FKIP ULM, 2019)
Abstract. This research is to see the implementation of Hangaroo Game and Word Jumble to build the students’ vocabulary mastery. The method used is quasi-experimental research. There were students of SMP Negeri 9 Banjarmasin as the sample. As the result, the students from both classes had limited comprehension on vocabulary proven by the students’ score of pre-test. The class of experimental yielded the mean score of 20,19. The mean score was 17,29. The final result of the research was determined after the researcher had acquired the t-test result. It is found that there was no difference of students’ vocabulary mastery taught using Hangaroo Game and students taught using Word Jumble. For further research, it is hoped to be more curious and innovative to choose other media that can be used to aid the students’ vocabulary mastery. Keywords: score, Hangaroo Game, Word Jumble, vocabulary, vocabulary mastery, Lexicogrammatical